ANNALYSIS OF Pb, Cu AND Zn METAL CONTENTS IN RED CHUT-CHUT SNAIL (Cerithidea obtusa) AND SEDIMENT IN MENDOL ISLAND KUALA KAMPAR OF RIAU PROVINCE - Sumanti, Susi; Nurrachmi, Irvina; Siregar, Yusni Ikhwan (Asian Journal of Aquatic Sciences, 2019)
The study was conducted in July 2018. Sampling of sedut snails (Cerithidea obtusa) which was carried out in the waters of Mendol Island, Kuala Kampar District, Pelalawan Regency was aimed to determine the differences in the content of Pb, Cu and Zn between slugs and sediments and to know the consumption limits and the level of heavy metal pollution in the waters of Mendol Island. The method used in this study is the survey method. Sampling was determined using purposive sampling. The results of this study indicate the value of the metal content of Pb, Cu, and Zn in sedut snail highest at station 2, respectively: 9,2633 μg / g, 72,040 μg / g, 111,748 μg / g. Whereas for Pb, Cu, and Zn metals, the highest sediment was found at station 2, namely: 23.990 μg / g, 4.795 μg / g, 48.587 μg / g The results of linear regression analysis of Pb metal concentrations in snail meat showed negative results, and the concentration of Zn and Cu metals in snail meat showed positive results. namely Pb with a value of 14.1930 kg / week on Zn metal with a value of 111.7483 kg / week, while Cu metal at station 2 with a value of 72.0400 kg / week